ҚАЗАҚ-ҚАРАҚАЛПАҚ ФОЛЬКЛОРЫ МЕНЕН ӘДЕБИЯТЫ БАЙЛАНЫСЛАРЫНЫҢ АЙЫРЫМ ӨЗГЕШЕЛИКЛЕРИ - Төрткүлбаева, Т. (SCIENCE and SOCIETY, 2017)
The article deals with the study Kazakh and Karakalpak influence, excessive improvement of national literature ideological thematic and genre, development from the point of view of form and achievement of national pecularity.